2006
DOI: 10.1021/la052599s
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometric Search for Vapor Layers at Liquid-hydrophobic Solid Surfaces

Abstract: We use precision ellipsometry to evaluate the existence of nanometer thick vapor films at the surface between a liquid and a hydrophobic alkylsilane coated Si wafer. We find no evidence for such vapor films. All of our fluid-solid ellipsometry measurements can be explained using a double layer model consisting of an oxide plus silane layer between the fluid and bulk Si substrate. We have carefully checked our ellipsometer for residual phase shifts which might, under certain circumstances, cause a mis-interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…We also note that extended depletion layers as extracted from the neutron data should also show up in optical ellipsometry where no such profiles were found (22,23). Furthermore, no indication for the influence of gases dissolved into the water on the hydrophobic gap (d Ͻ 2.5 Å) was found in heat conductance measurements (24).…”
Section: Resultsmentioning
confidence: 76%
“…We also note that extended depletion layers as extracted from the neutron data should also show up in optical ellipsometry where no such profiles were found (22,23). Furthermore, no indication for the influence of gases dissolved into the water on the hydrophobic gap (d Ͻ 2.5 Å) was found in heat conductance measurements (24).…”
Section: Resultsmentioning
confidence: 76%
“…This agreed with the literature in that few nanobubbles can be detected simply by immersing a hydrophobic substrate in water. 20,57,58 Zhang et al 59 reported that interfacial nanobubbles were not observed when a smooth OTS-Si wafer was placed in a CO 2 -saturated water solution, and the interfacial bubbles are formed only through a fast solvent exchange treatment. It is widely accepted that the fast variation of gas solubility in water solution is key to inducing the nucleation of nanobubbles.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a correlation between water density and hydrophobicity reflects the complexities present in realistic systems arising from different molecular topologies and different head group water interactions. It also highlights and probably rationalizes the difficulty in obtaining unambiguous conclusions from experiments regarding wetting/dewetting of realistic hydrophobic interfaces (27)(28)(29)(30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 81%
“…Although a number of experimental tools including X-ray (27)(28)(29)(30)(31) and neutron reflectivity (32,33), ellipsometry (34), and thermal conductivity (35) have been used to probe the width of the ''depletion layer'' at a hydrophobic surface, a clear picture has not yet emerged from these measurements (42). Fig.…”
mentioning
confidence: 99%